KREATIFITAS WIRAUSAHA KELOMPOK IBU TANI DALAM MENINGKATKAN NILAI EKONOMIS HASIL PANEN BAWANG MERAH UNTUK KESEJAHTERAAN MASYARAKAT - Bachtiar, Yusran; Nirwana Sampara (Universitas Muhammadiyah Parepare, 2020)
Onion farmers in Enrekang district are scattered in almost every sub-district, one of them is in Baraka sub-district. The produced shallots are very abundant but unfortunately this is not enough to sustain the farmers' economy, this is due to the weak value of creativity due to limited science and technology utilization, onion marketing which is still traditional by relying on local local markets and collectors so that the selling price is relatively low. The goal to be achieved in this activity is to foster a spirit of creativity of the farmers in order to increase the value of economic prosperity. By way of training and coaching for the sake of giving birth to products and business spirit, starting with a review of market opportunities, market sales promotion techniques both in a modern and online way supported by good management and accountable financial management. The product offering is fried onions using simple technology in the form of Multy Cutters as a cutting tool and spinner machine as an oil filter. The activities carried out through several stages, namely: (1) the stage of program socialization, (2) the training stage for empowerment of farmer groups, (3) the stage of skills development and (4) the stage of monitoring and evaluation. The results carried out in this activity can increase knowledge and skills and can increase the economic income of citizens.